Solar based plant care system - Lee, Sheryl Xin Ting (Nanyang Technological University, 2022)
Sustainability has always been an area of interest in conventional and urban farming. Current research focuses on using innovative practices and methods to tackle water scarcity for production, enhance food security, and improve plant growth with minimal human intervention while reducing adverse effects on the environment.